1993
DOI: 10.1055/s-0038-1651637
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Polymorphism in Glycoprotein IV (Replacement of Proline-90 by Serine) Predominates in Subjects with Platelet GPIV Deficiency

Abstract: SummaryTo clarify the molecular basis of the deficiency of glycoprotein IV (GPIV) of the platelet surface, we analyzed GPIV cDNA synthesized from platelet RNA of five unrelated Japanese subjects whose platelets did not express GPIV.We confirmed the presence of normal-sized GPIV mRNA in platelets from subjects with GPIV deficiency. The sequence of platelet GPIV cDNA from GPIV deficient subject showed three differences when compared with the published sequence; 1) a replacement of a 478CCT codon for proline-90 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 7 publications
0
36
0
Order By: Relevance
“…In patients with CD36-D, compared with healthy CD36-positive controls, metabolic phenotypes such as high TG levels, low HDL-C levels, high fasting glucose and hypertension were observed more frequent- 7,9) . Furthermore, we also found that patients with CD36-D are accompanied by insulin resistance 10) , postprandial hyperlipidemia, and high levels of remnant lipoprotein cholesterol and FFA [8][9] .…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In patients with CD36-D, compared with healthy CD36-positive controls, metabolic phenotypes such as high TG levels, low HDL-C levels, high fasting glucose and hypertension were observed more frequent- 7,9) . Furthermore, we also found that patients with CD36-D are accompanied by insulin resistance 10) , postprandial hyperlipidemia, and high levels of remnant lipoprotein cholesterol and FFA [8][9] .…”
Section: Discussionmentioning
confidence: 89%
“…In order to confirm the diagnosis of CD36-D in these patients, immunofluorescent flow cytometric analysis was performed by using mouse monoclonal antibodies against CD36 (OKM5; Ortho Diagnostic System Inc., Raritan, NJ) at the Department of Blood Transfusion, Osaka University Hospital 7) . Briefly, 20 ml of blood was drawn, anticoagulated with heparin (10 U/ml), layered over 10 ml FicollPaque (GE Healthcare UK Ltd., Buckinghamshire, UK) and centrifuged at 1,000 g for 30 minutes.…”
Section: Diagnosis Of Cd36 Deficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…The physiological function of CD36 has not been well characterized although it was proposed to be a receptor for both thrombospondin and collagen or to mediate cytoadherence of plasmodium falciparum parasitized erythrocytes (17)(18)(19)(20). From the research on the subjects refractory to HLA-matched platelets transfusion (21)(22)(23)(24), Kashiwagi et al have identified the subjects whose platelets and monocytes lack CD36, and clarified three types of gene abnormalities (substitution of Pro' by Ser, deletion of two bases in exon 5, and insertion of one base in exon 10; Kashiwagi, H., Y. Tomiyama, S. Nozaki, S. Honda, H. Mizutani, S. Kosugi, M. Shiraga, N. Nagao, Y. Kanakura, Y. Kurata, and Y. Matsuzawa, manuscript in submission) (25,26). All these abnormalities result in the absence of CD36 expression on the cell surface.…”
Section: Introductionmentioning
confidence: 99%